Cimicifugae Rhizoma Extract Attenuates Oxidative Stress and Airway Inflammation via the Upregulation of Nrf2/HO-1/NQO1 and Downregulation of NF-κB Phosphorylation in Ovalbumin-Induced Asthma - Je-Oh Lim; Kwang Hoon Song; Ik Soo Lee; Se-Jin Lee; Woong-Il Kim; So-Won Pak; In-Sik Shin; Taesoo Kim (MDPI AG, 2021)
Cimicifugae Rhizoma has been used as a medicinal herb for fever, pain, and inflammation in East Asia. We conducted this study because the effect of Cimicifugae Rhizoma extract (CRE) on allergic asthma has not yet been evaluated. To induce allergic airway inflammation, we intraperitoneally injected ovalbumin (OVA) mixed with aluminum hydroxide into mice twice at intervals of 2 weeks (Days 0 and 14) and then inhaled them thrice with 1% OVA solution using a nebulizer (Days 21 to 23). CRE (30 and 100 mg/kg) was administered orally daily for 6 days (Days 18 to 23). The mice showed remarkable reduction in allergic inflammation at 100 mg/kg of CRE, as evidenced by decreased inflammatory cell counts, pro-inflammatory cytokine levels, OVA-specific immunoglobulin E level, airway hyperresponsiveness, and production of mucus. Additionally, these effects were involved with the enhancement of heme oxygenase-1 (HO-1), NAD(P)H: quinone oxidoreductase (NQO1), and nuclear factor erythroid 2-related factor 2 (Nrf2) expression and reduction of nuclear factor-κB (NF-κB) phosphorylation and matrix metalloproteinase-9 expression. Our findings indicated that CRE effectively protected against OVA-induced inflammation and oxidative stress via upregulation of the Nrf2/HO-1/NQO1 signaling and downregulation of NF-κB phosphorylation in asthma caused by OVA.